General Soedirman: History Learning Media Based on Digital Comics - Nugroho, Alifi Nur Prasetia; Adeduntan, Ronke Iyabo; Tariq, Ateeq Ahmad (Journal Evaluation in Education (JEE), 2024)
Purpose of the study: This research aims to address the low student interest and engagement in the history learning subjects of General Soedirman’s Guerrilla War by developing a digital comic-based history learning media and examining its effectiveness in enhancing the student learning motivation and achievement. Methodology: The research uses the Research and Development (R&D) method adapted from the ADDIE development design. The research subjects are 20 students in senior high school in Surakarta and Pakistan. The data collection technique is a test. Main Findings: The research data shows that the digital comic-based history learning media of General Soedirman’s Guerrilla War is effective and suitable for use. The validation by material experts shows that the learning media material has a very good quality with an average score of 89.6%. The media validation results show that the learning media is very good and suitable for application in the learning process with an average score of 84.6%. The results of the One-to-one Test, Small Group Test, and Field Test show that the learning media can improve the student learning motivation and achievement with an average score of 71.4%, 74.2%, and 78.8%, respectively, exceeding the expected outcome of 70%. Novelty/Originality of this study: The research novelty to develop a digital comic-based history learning media of General Soedirman’s Guerrilla War, which is a significant historical event in Indonesia. The research has implications for the improvement of the history curriculum and the student learning interest and engagement in history subjects.”